A longitudinal study of well-being, confidence and competence in junior doctors and the impact of emergency medicine placements. Issue 2 (3rd September 2015) - Mason, Suzanne; O'Keeffe, Colin; Carter, Angela; Stride, Chris
Abstract : Objectives: To measure levels of, and change in junior doctor well-being, confidence and self-reported competence over their second postgraduate training year and the impact of emergency department (ED) placements on these outcomes. Design: A longitudinal study using an online survey administered at four time points (2010–2011). Setting: 28 Acute Hospital Trusts, drawn from nine participating Postgraduate Deaneries in England. Participants: Junior doctors who had a placement in an ED as part of their second postgraduate training year. Main outcome measures: Levels of anxiety, depression, motivation, job satisfaction, confidence and self-reported competence, collected at four time points spread over the period of the doctor's second training year (F2). Results: 217 junior doctors were recruited to the study. Over the year there was a significant increase in their overall job satisfaction, confidence and self-reported competence. Junior doctors also reported significantly increased levels of motivation and anxiety, and significantly decreased levels of extrinsic job satisfaction when working in ED compared with other specialties. There were also significant increases in both junior doctor confidence and self-reported competence after their placement in ED relative to other specialties. Conclusions: While elements of junior doctor well-being worsened in their ED placement compared with their time spent in other specialties, the increased levels of anxiety and reduced extrinsic job satisfaction were within the normal range for other healthcare workers. These deficits were also balanced by greater improvements in motivation, confidence in managing common acute clinical conditions and perceived competence in performing acute procedures compared with benefits offered by placements in other specialties.